PENERAPAN AUGMENTED REALITY PENGENALAN JENIS OLAHRAGA BERBASIS ANDROID - Rendi, Alvin; Handoko, Koko (Computer Science and Industrial Engineering, 2021)
Developments that unite science and technology form a new invention, namely the smartphone. In the world of education, smartphones are effective learning tools that can be used anywhere. Learning media in the form of technology on smartphones is Augmented Reality in learning introduction to sports. Augmented Reality is a technology that combines 2D and 3D virtual objects into an interactive real-time environment. Changes in learning methods lead to digital based using computer technology that accepts inputs such as audio and video. The support of the Blender sports software is made into 3D, the Vuforia database and the Unity Engine as software used to develop Augmented Reality applications using the C# programming language. The resulting application is an Augmented Reality application with virtual sports objects in 3D and can be displayed in real time. Marker is a pattern or marker in the form of an image that will be recognized by the camera by pointing the camera on the smartphone to the marker that has been printed, then the 3D object will be displayed on the smartphone. The use of Augmented Reality technology is expected to be an alternative media, so that it is interesting and varied in learning about sports.